Implementasi Statistical Quality Control pada Produksi Batu Bata di Desa Lambaro Sukon, Aceh Besar - Newton Newton; Miftahuddin Miftahuddin (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2026)
Quality control in small-scale traditional industries such as brick manufacturing often relies on experience rather than systematic statistical methods. This community service activity was conducted at Cahaya Fajar Brick Factory, located in Lambaro Sukon Village, Darussalam District, Aceh Besar Regency, on November 16, 2025. The objective of this activity was to introduce and apply Statistical Quality Control (SQC), specifically Control Charts for Variables (X̅–R Chart), to monitor and control the dimensional consistency of brick products measuring 4 × 10 × 22 cm. The method used included direct observation, interviews with factory owners, and quantitative data collection from the production process. The results showed that the factory’s daily production capacity reached approximately 5,000 bricks with a defect rate of only 0.5% per batch of 8,000 bricks. Statistical analysis revealed that drying duration (7 versus 20 days) did not significantly affect the proportion of cracked bricks (z = −1.30, |z| < 1.96). The application of control charts is recommended for monitoring dimensional variation, detecting special cause variations caused by raw material quality, weather, and worker technique differences, as well as improving production consistency in the long term.